Pengaruh Pengawasan Terhadap Kinerja Pegawai Aviation Security Di Bandar Udara Djalaluddin Gorontalo - Dwiki Ramdani; Darmawaty Abd. Razak; Sandi Prahara (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2022)
Performance is the result or all major achievements of a person during a certain period in completing a task compared to other possibilities, for example, work guidelines, goals or targets and measures that have been completed previously and have been generally agreed upon. External factors that affect employee performance are supervision. This study is to determine whether supervision has an effect on the Performance of Aviation Security Employees (AVSEC) at Djalaludin Airport Gorontalo. This research method is a survey method by taking a sample of 70 respondents using a saturated sampling technique (census) using a questionnaire instrument. The analytical method used is correlation analysis, coefficient of determination and simple regression analysis processed through the SPSS 21 program. The results show that there is a positive influence of supervision (X) on the performance (Y) of Avsec employees at Djalaludin Airport Gorontalo by 0.355 (35.5% ). As for 0.645 (64.5%) is influenced by other variables that are not studied in the form of work discipline, work motivation and so on. The results of the study using the Supervision correlation test on Avsec Employee Performance at Djalaludin Airport Gorontalo there was a moderate level of relationship (r = 0.596).